2020
DOI: 10.26442/00403660.2020.09.000742
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and cardiovascular diseases

Abstract: First cases of new coronavirus infection were registered in December 2019. The COVID-19 outbreak was declared a global pandemic. COVID-19 is much more dangerous for people older than 65. It is well known that cardiovascular diseases are more affecting older patients as well. The potentially dangerous combination of the new infection and different cardiovascular diseases has become a crucial problem of cardiology in 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…[27] According to these studies, the inflammatory process plays a key role in the pathogenesis of heart failure. Dunley et al in the Olmsted County study concluded that the level of (TNF)-α in patients with HF with a preserved ejection fraction was higher and directly correlated with mortality in this group of patients [28]. (прошлая версия): Pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1 and IL-6 play an important role in the pathogenesis of heart failure.…”
Section: Commented [1]: Describe Ferritin Data??mentioning
confidence: 99%
“…[27] According to these studies, the inflammatory process plays a key role in the pathogenesis of heart failure. Dunley et al in the Olmsted County study concluded that the level of (TNF)-α in patients with HF with a preserved ejection fraction was higher and directly correlated with mortality in this group of patients [28]. (прошлая версия): Pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1 and IL-6 play an important role in the pathogenesis of heart failure.…”
Section: Commented [1]: Describe Ferritin Data??mentioning
confidence: 99%
“…К наиболее значимым механизмам декомпенсации ХСН при инфицировании вирусом SARS-CoV-2 относят: негативное влияние лихорадки любого происхождения на водно-солевой обмен и увеличение нагрузки на сердце; повреждение мио карда, опосредованное избыточной активацией цитокинов; прямое действие вируса на кардиомиоциты с развитием миокардита [2]. Значимость вклада имеющейся органической патологии сердца в контексте легочных осложнений COVID-19 варьирует от наличия классической ХСН с сохраненной фракцией выброса левого желудочка (ФВ ЛЖ) до развития острой систолической сердечной недостаточности как патологического ответа на цитокиновую фазу течения COVID-19.…”
Section: ключевые моменты что известно о предмете исследования?unclassified
“…Значимость вклада имеющейся органической патологии сердца в контексте легочных осложнений COVID-19 варьирует от наличия классической ХСН с сохраненной фракцией выброса левого желудочка (ФВ ЛЖ) до развития острой систолической сердечной недостаточности как патологического ответа на цитокиновую фазу течения COVID-19. После перенесенной COVID-19 у большинства пациентов наблюдается декомпенсация ХСН, что связывают с возникновением фиброзных изменений в легочной ткани и миокарде [2].…”
Section: ключевые моменты что известно о предмете исследования?unclassified
“…In addition, an increase in the incidence of cardiovascular events after recovery from COVID-19 may also play a role in the increase in mortality [6,7,8].…”
Section: Relevance Of the Problemmentioning
confidence: 99%